Sustainable urban regeneration in port-cities. A participatory project for Genoa waterfront - Pirlone, Francesca; Spadaro, Ilenia; Sabattini, Martina; De Nicola, Marco (TeMA - Journal of Land Use, Mobility and Environment, 2022)
The scope of this document is to develop a methodological approach, and at the same time providing design applications, in terms of urban regeneration. An increasingly emerging topic in our urban realities. In particular, a systematic analysis of practices and models is reported, in the current context of urban planning, in the regeneration of port-cities. The paper reports a research developed in the university field starting from a public competition. The research starts from the definition of urban regeneration to arrive at the identification of an circular approach and key issues applicable to the Genoa Pra’-Palmaro case study. According to the “learning-by-doing” approach, the Pra’-Palmaro case study is analyzed here to highlight the strategies implemented for a multi-disciplinary and multi-stakeholder urban regeneration project. The research output is a methodological approach that supports the realization of an urban regeneration process thus opening a scientific debate on the topic. Particular attention is paid to current policies and strategies related to concepts such as: sustainability, circular economy, resilience and new technologies. The research can therefore help other port-cities in the world to realize sustainable urban regeneration, also attentive to the participation and involvement of stakeholders.